A Multidimensional Research Strategy for the Evaluation of Settlement Pits: 3D Electrical Resistivity Tomography, Magnetic Prospection and Soil Chemistry. Issue 4 (26th June 2015) - Nowaczinski, Erich; Schukraft, Gerd; Rassmann, Knut; Reiter, Samantha; Müller‐Scheeßel, Nils; Hecht, Stefan; Eitel, Bernhard; Bubenzer, Olaf; Bátora, Jozef
Abstract: Irrespective of the region and time period, settlement pits are common features at archaeological sites. Variations in shape, size and fill reflect great diversity in terms of primary and secondary functions. Careful analysis of these aspects and a pit's refilling history yield key information for the reconstruction of economic, social and chronological aspects of settlement history. At present, it is unusual for a settlement site to undergo complete excavation; in most cases, only small areas within a larger settlement are opened to archaeological inquiry and, accordingly, only a scarce few pits can be excavated. Therefore, the application of a combination of new prospection methods can help to classify and preselect representative pits for subsequent excavation in order to guarantee the highest information output. The interdisciplinary investigations at the Early Bronze Age of Fidvár in Slovakia enabled the development of just such a multidimensional research strategy for the evaluation of settlement pits. Used in concert, magnetic survey and electromagnetic prospection delivered 2D data which revealed the locations of pits at the site. This was the basis for the 3D electrical resistivity tomography measurements which followed, enabling the three‐dimensional reconstruction of prehistoric pits' geometries. Supplementary sedimentological and geochemical investigations of the pits' contents revealed important information about the pits' former functions as well as the mechanisms of the processes through which they were filled in. Thus, the integrated approach provides us with a new means of obtaining an overview of pit assemblages at archaeological sites in general and demonstrates its potential for the acquisition of valuable information about the food acquisition and storage processes at Fidvár in specific. Copyright © 2015 John Wiley & Sons, Ltd.